IMPLEMENTASI PERATURAN PRESIDEN NOMOR 19 TAHUN 2016 TERHADAP KEWAJIBAN KARYAWAN PERUSAHAAN MENJADI PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) - Ratna Mayasari (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT "Implementation of Presidential Regulation Number 19 of 2016 Against Obligations of Company Employees Being Participants Social Security Administering Board (BPJS)" This study was conducted to determine the procedure Social Security Administering Agency (BPJS) to employees of the Company as a participant BPJS and Implementation where in data collection, Normative methods from various literature sources such as library materials, Laws, Presidential Regulations that provide a very clear picture of the implementation of Presidential Regulation Number 19 of 2016 on the obligations of employees of the company to be a participant of the Social Security Administering Agency (BPJS). The results of the study indicate that based on Presidential Regulation Number 19 of 2016 concerning the Second Amendment to Presidential Regulation Number 12 of 2013 on Health Insurance all must submit and comply with the provisions in question. Employers are still there who have not implemented or violated because it is in need supervision and guidance by agencies related to the existence of sanctions that have been arranged. Keywords: Presidential Regulation Number 19 of 2016, Implementation, Company     Employee, Social Security Administering Board (BPJS).